PEMBENTUKAN MODEL PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN BUDAYA KEWIRAUSAHAAN UNTUK MENGURANGI PENGANGGURAN DAN KEMISKINAN - Sukhemi, Sukhemi; Maisaroh, Siti (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2019)
ABSTRACT   This study aims to examine the model’s formation that can reduce the problem of unemployment and poverty. In accordance with these objectives,  there are several principal problems studied in this research that are; (1) how the approach to poverty reduction programs should be made, (2) how the potential of local institutions' resources are able to act as virtuous circles to reduce the poverty, (3) how the community empowerment model system based on the potential of local wisdom resources and institutions local communities should be conducted in order to be able to significantly reduce the number of local poor community, independent and sustainable. This research was conducted at Muntuk Village due to it is classified as a backward village and it still has the good local wisdom potential to be developed further. This research applies participatory research method to the craftsmen group chosen as pioneer in forming the community empowerment model. The main subjects in this research are; craftsmen group and socio economic community societies at Muntuk Village. The subjects of this study are determined by purposive sampling. Data collection techniques are done through interview, FGD, and analytical descriptive analysis. The result of the research shows that the link and the integration among the bamboo handicraft industry, the local institution’s role, the entrepreneurship spirit and the work ethic of the craftsmen group through the entrepreneurial skills development and social entrepreneurship culture are able to be a virtuous circle or the virtue circle to cut the poverty problem, more independent and sustainable, from the original still powerless to be powerful. The strengthening of empowerment model supported by the strength of human capital, social capital, and also citizens participate actively, were increasingly able to produce a form of community empowerment model. Furthermore, the empowerment model is more strongly built through six pillars namely; industrial structure, entrepreneurship spirit, human capital and social capital factors, local institution, infrastructure and conductive environment. All sub-systems in each of these pillars are interconnected in a system namely community empowerment system model through the development of an entrepreneurial culture to alleviate unemployment and poverty. Keywords : Empowerment Model, Enterpreneur Culture, Unemployment and Poverty